Solid state nuclear track detectors : proceedings of the 10th International Conference, Lyon, 2-6 July 1979 - Francois, Henri, 1926- (Pergamon Press, 1980)
Solid State Nuclear Track Detectors is a collection of papers that covers various aspects of solid state nuclear track detectors. The book presents 130 articles that cover the concerns in the mechanisms, operations, and applications of solid state nuclear track detectors. The materials in the text are thematically grouped into three parts. The book first discusses the fundamental mechanisms, which include determination of the screening parameter from measurements of differential energy loss and atomic displacement effects from heavy ion induced coulomb explosion. Next, the selection presents a.